2021
DOI: 10.3390/ijms22041889
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic Acid-Loaded β-TCP Inhibits Tumor Proliferation and Osteoclast Activation: Development of a Functional Bone Substitute for an Efficient Osteosarcoma Treatment

Abstract: Osteosarcoma has a poor survival rate due to relapse and metastasis. Zoledronic acid (ZOL), an anti-resorptive and anti-tumor agent, is used for treating osteosarcoma. Delivery of ZOL to the target region is difficult due to its high binding affinity to bone minerals. This study developed a novel treatment for osteosarcoma by delivering ZOL to the target region locally and sustainably. In this study, we fabricated a novel bone substitute by loading ZOL on β-tricalcium phosphate (β-TCP). The ZOL-loaded β-TCP (Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In our models, reducing oestradiol to peri- or post-menopausal concentrations significantly reduced bone volume through increased osteoclast activity, as is also observed in women during the same representative stages of menopause, providing evidence that our model is representative of the human condition ( 32 , 33 ). Zol has well-characterised properties of inhibiting bone resorption via preventing osteoclast activity and causing osteoclast apoptosis in both mouse models and humans ( 34 36 ). Our data suggest that the ability of Zol to reduce osteoclastic bone resorption is not affected by oestradiol ( Figures 1 , 7 ), and in the absence of tumour, Zol increases bone mass under pre-, peri-, and post-menopausal concentrations of this hormone.…”
Section: Discussionmentioning
confidence: 99%
“…In our models, reducing oestradiol to peri- or post-menopausal concentrations significantly reduced bone volume through increased osteoclast activity, as is also observed in women during the same representative stages of menopause, providing evidence that our model is representative of the human condition ( 32 , 33 ). Zol has well-characterised properties of inhibiting bone resorption via preventing osteoclast activity and causing osteoclast apoptosis in both mouse models and humans ( 34 36 ). Our data suggest that the ability of Zol to reduce osteoclastic bone resorption is not affected by oestradiol ( Figures 1 , 7 ), and in the absence of tumour, Zol increases bone mass under pre-, peri-, and post-menopausal concentrations of this hormone.…”
Section: Discussionmentioning
confidence: 99%
“…The US Food and Drug Safety Administration also approved zoledronic acid in combination with systemic therapy for the treatment of patients with bone metastases from solid tumors because it has been shown to be effective against many types of solid tumors ( Santini et al, 2003 ; Rosen et al, 2004 ; Hatoum et al, 2008 ). Published studies have shown that zoledronic acid has therapeutic effects on tumors, including osteosarcoma by inhibiting cell proliferation and motility and inducing apoptosis and autophagy ( Kubista et al, 2006 ; Dass and Choong, 2007 ; Oh et al, 2019 ; Kameda et al, 2021 ; Liu et al, 2021 ). However, it is not clear whether zoledronic acid can inhibit the growth of cancer cells including osteosarcoma cells through inducing ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…CRIg–CD59 was first encapsulated into ZIF8 nanoparticles; after that hydroxyapatite (HA) layers were coated on the surface of the ZIF8 to prevent its rapid decomposition in acidic environments and achieve sustained release of CRIg–CD59. More importantly, zoledronic acid (ZA) was grafted onto the surface of HA-decorated ZIF8 nanoparticles for targeted delivery to bone minerals and inhibition of bone resorption. , After CRIg–CD59 was released in the joint, the targeting activity of CRIg to C3 cleavage products enabled the recombinant protein to reach the complement-activated cell surface, and CD59 competitively inhibited the binding of C5b-8 and C9, thereby inhibiting the MAC formation and complement cascade. In addition, the competitive binding of CRIg to C3 cleavage products can inhibit the cross-talk of complement and nonspecific immunity, and inhibit the production of inflammatory factors such as TNF-α, IL-1, and IL-6.…”
Section: Introductionmentioning
confidence: 99%